2022
DOI: 10.3389/fcell.2022.1003767
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mortality in acute lung injury induced by oleic acid: Application of polyherbal decoction (bronco T)

Abstract: Acute lung injury (ALI) is a lethal respiratory disorder; directed uncontrolled inflammation, sloughing of the alveolar cells and their diffusion, and altered cardiorespiratory parameters with a global mortality rate of 40%. This study was designed to assess the preventive effect of a polyherbal decoction (Bronco T, 1.5 g/kg b. w.) on cardiorespiratory variables in oleic acid-induced ALI in rats. Oleic acid increases the level of neutrophil infiltration leading to pulmonary edema and alters the cardiorespirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Oleic acid decreases alveolar surfactant, resulting in pulmonary edema. 79 , 80 Ferroptosis has distinct morphological characteristics that differ from other cell death types. Existing studies have identified that ferroptosis is morphologically characterized by reduced mitochondria, ruptured mitochondrial membrane, reduced mitochondrial ridges, and reduced mitochondrial size.…”
Section: Ferroptosis and Alimentioning
confidence: 99%
“…Oleic acid decreases alveolar surfactant, resulting in pulmonary edema. 79 , 80 Ferroptosis has distinct morphological characteristics that differ from other cell death types. Existing studies have identified that ferroptosis is morphologically characterized by reduced mitochondria, ruptured mitochondrial membrane, reduced mitochondrial ridges, and reduced mitochondrial size.…”
Section: Ferroptosis and Alimentioning
confidence: 99%